Influence of teacher autonomy support in feedback on high school students’ feedback literacy: the multiple mediating effects of basic psychological needs and intrinsic motivation - Zhang, Shang; Xu, Jie; Chen, Hao; Jiang, Lan; Yi, Xinfa (Frontiers in Psychology, 2024)
This research presents and confirms an intermediary model, deeply anchored in self-determination theory, to dissect the influence of Chinese high school students’ core psychological needs and intrinsic drive on the nexus between educators’ autonomous backing and students’ proficiency in feedback literacy, highlighting the mediating roles of these elements. A survey of 704 Chinese senior high school students, including 319 males and 385 females, employed the Feedback Literacy Scale, Basic Psychological Needs Scale, Intrinsic Motivation Scale, and Perceived Teacher Autonomy Support Scale. The study’s discoveries illuminate that educators’ autonomous support not only directly amplifies students’ feedback literacy but also has an indirect impact through the intermediation of basic psychological needs and intrinsic motivation, along with their interconnected dynamics. This inquiry not only deepens our grasp of the mechanisms interlinking teacher support with feedback literacy but also critically evaluates the findings to proffer targeted recommendations, thereby enhancing our comprehension of the underlying processes and guiding educational practices and student development.